Illegal Hunting Prevention by Indigenous People in Bromo Tengger Semeru National Park - Hablana Rizka Achmadi; Adelia Ramadhani Savitri; Adhe Puspawari Hardhany; Ayu Rini Tirtasari Haryono; Muh. Danny Wirawan (Jurnal Hukum Novelty, 2019)
Introduction to The Problem: National park is a conservation area which has the most advanced management system compared to forest park, Nature Park, nature reserves, and wildlife reserves. The national park is becoming the area that can anticipate the hunt and to prevent the extinction of protected animals. One of the largest national parks in East Java is Bromo Tengger Semeru. Around the park, there lived a Tengger tribe whose role is to maintain the conservation areas.Purpose/Objective Study: The purpose is to determine the response on illegal hunting conducted by people around Bromo Tengger Semeru National Park and to determine the factors supporting the illegal hunting prevention in Bromo Tengger Semeru National Park.Design/Methodology/Approach: The type of this study is sociological law study using qualitative methodology — the data collected through observation, interviews, and literature.Findings: The results show that the way the Tengger tribe prevent illegal hunting is by doing spiritual guidance. While the supporting factors in preventing illegal hunting is the law and legal custom owned by Tengger tribe, thus the customary law applied by Tengger tribe is more effective than national law.